A systematic review protocol of stigma among children and adolescents with epilepsy - Kirabira, Joseph; Forry, Jimmy Ben; Kinengyere, Alison Annet; Adriko, Wilson; Amir, Abdallah; Rukundo, Godfrey Zari; Akena, Dickens (Systematic Reviews, 2019)
Background: Epilepsy is a neurological condition that is highly prevalent among children and adolescents with 80% of the victims living in low- and middle-income countries (LMIC). Epilepsy is associated with high levels of both perceived and enacted stigma, which vary geographically and greatly affects the victims’ quality of life and self-esteem. High rates of stigma are also a significant barrier to accessing medical care. Perceived and enacted epilepsy-related stigma is associated with various sociodemographic and clinical factors, which vary from place to place. Therefore, this review will determine the prevalence of stigma of epilepsy among children and adolescents and the associated factors worldwide. Methods: We will search for literature in PubMed, EMBASE, PsycINFO, and CINAHL databases as well as grey literature. We will also search via Google Scholar to capture relevant literature that may not be in the searched databases. We will then screen reference lists of included studies for more studies. Studies that have documented the prevalence of epilepsy-related perceived or enacted stigma and the associated factors will be eligible for inclusion. Data will be extracted in duplicates using a pre-piloted tool consisting of study and participant characteristics as well as pre-determined factors associated with epilepsy. Heterogeneity will be assessed by a forest plot and quantified by I2 statistic, and in case it is high, results will be reported as a narrative and it will further be explored by subgroup analysis. In case of homogeneity, meta-analysis will be done. Bias will be assessed using a critical appraisal tool developed for prevalence studies. The strength of evidence among the studies will be assessed using the GRADE approach. Discussion: Findings from this review will document the burden of stigma of epilepsy and the common contributing factors, which will form the building blocks of interventions that address this health challenge
Keywords: Stigma; Epilepsy; Children; Adolescents; Prevalence